ANALISIS KEMANDIRIAN BELAJAR DALAM PEMBELAJARAN MATEMATIKA PADA SISWA SMP - Ira Fitria Rahayu; Indrie Noor Aini (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This research is conducted to describe student’s Self Regulated Learning in mathematics subject. Methods in this research is qualitative approach with descriptive method. Subjects in this research is students in Junior High School in Kabupaten Karawang with total subject is 25 students. Techniques that use in this research to collect the data is distribute the questionnaires of Self Regulated Learning that consist of 30 question with 8 indicator. Data analysis techniques used by the percentage formula of student answers and described using criteria interpretation percentage of answers. The result of this research is shows that average of all the Self Regulated Learning in studying is 56,85% that obtains from 25 students who filled out the questionnaires. Based on those percentage,it shows that mostly the students are capable to Self Regulated Learning, but remember the importance of Self Regulated Learning that must be always imporoved.